Subspecies discrimination based on song structure by Willow Flycatchers. Issue 2 (26th May 2021) - Mahoney, Sean M.; Pasch, Bret; Theimer, Tad C.
Abstract: Animals use acoustic signals to repel competitors and attract mates, and signal divergence among populations can promote reproductive isolation. Empidonax flycatchers are insectivorous songbirds distributed across North and Central America that are conservative in plumage, but often exhibit differences in songs both among and within species. Four subspecies of Willow Flycatchers ( Empidonax traillii ) have been recognized and previous analyses have revealed differences in song structure among a subset of these subspecies. Using reciprocal playback experiments in the field, we tested for subspecific song discrimination among these four putative subspecies of Willow Flycatchers. We found that three subspecies ( E. t. adastus, E. t. brewsteri, and E. t. traillii ) responded similarly to their own songs and those of each other, but all three subspecies responded significantly less aggressively to songs of the southwestern subspecies ( E. t. extimus ). In contrast, the southwestern subspecies ( E. t. extimus ) responded significantly more aggressively to its own song than to those of the other three subspecies. Our results indicate that behavioral responses reflect differences in song structure among subspecies; subspecies responded more strongly to songs of subspecies with similar structures, less strongly to songs most different in structure, and the subspecies with the most distinctive song ( E. t. extimus ) responded less to songs of the other three subspecies. If responses of males to songs reflect relative reproductive compatibility within and among subspecies, songs may contribute to reproductive isolation of the four subspecies of Willow Flycatchers. RESUMEN: Discriminación de subespecies de Empidonax traillii con base en la estructura del canto Los animales usan señales acústicas para repeler competidores y atraer parejas y la divergencia en la señal entre poblaciones puede promover aislamiento reproductivo. Atrapamoscas en el género Empidonax son aves insectívoras distribuidas a lo largo de Norte y Centro América que tienen plumaje conservado filogenéticamente, pero con frecuencia muestran diferencias en cantos dentro y entre especies. Se reconocen cuatro subespecies de Empidonax traillii y análisis previos han revelado diferencias en la estructura del canto entre un sub grupo de estas subespecies. Usando experimentos de playback recíprocos en el campo, evaluamos la discriminación subespecífica del canto entre estas cuatro subespecies putativas de Empidonax traillii . Encontramos que tres subespecies ( E. t. adastus, E. t. brewsteri, y E. t. traillii ) respondieron similarmente a su propio canto que al de otras subespecies, pero las tres subespecies respondieron significativamente menos agresivamente a cantos de la subespecie del suroeste ( E. t. extimus ). En contraste, la subespecie del suroeste ( E. t. extimus ) respondió significativamente más agresivamente a su propio canto que a los de las otras tres subespecies. Nuestros resultados indican que las respuestas comportamentales reflejan diferencias en la estructura del canto entre subespecies; subespecies responden más fuertemente a cantos de subespecies con estructura similar, menos fuertemente a cantos con mayores diferencias en la estructura y las subespecies con el canto más diferente ( E. t. extimus ) respondieron menos a los cantos de las otras tres subespecies. Si las respuestas de los machos reflejan la compatibilidad reproductiva relativa dentro y entre subespecies, los cantos pueden contribuir al aislamiento reproductivo de las cuatro subespecies de Empidonax traillii .